Cross-Cultural Communication Theory - Fadhilah, Nurul (PT. Anagata Sembagi Education, 2024)
Humans, influenced by their environment and culture, form diverse characters. Tolerance and openness between cultures is the key to coexistence. Joining a group brings a solution in culture, even if it conflicts with individual personalities. Dynamics and interactions between groups are needed to find a new culture, despite the potential for clashes due to cultural defenses. This phenomenon often occurs in students who migrate, facing culture shock due to cultural differences. Adjustment to the new environment is needed to overcome culture shock. Skilled adaptation communication can minimize the impact of culture shock and prevent conflict. This research uses descriptive qualitative methods with secondary data. Adaptation communication patterns of overseas students involve four stages: self-adjustment, frustration, readjustment, and development of meaningful communication. These four stages become the facility and heart of successful adaptation, improving students' communication and social relations with the campus environment.